Helix Light Vortex Theory (HLV) - Marcel Krüger (Marcel Krüger born 18.07.84, 2025)
Paradigms Following the Experimental Confirmation of Spiral-induced Bio-Gravimetric -Helix Light Vortex Theory
Paradigms Following the Experimental Confirmation of Spiral-induced Bio-Gravimetric -Helix Light Vortex Theory